Ecosystem services to promote Conservation Agriculture practices in Morocco: Challenges and opportunities - Dahan, Rachid; Moussadek, Rachid (2023)
In Morocco, the low-input cropping systems dominated by cereal monoculture and intensive tillage have a marked negative impact on pressure from diseases, weeds and pests resulting in decreased profit margins. This form of agriculture is considered to act as a major driver of biodiversity loss and to speed up the loss of soil by increasing the mineralization of organic matter and erosion rates. It is also causing adverse effects on major soil functions, viz. primary productivity, carbon sequestration and regulation, nutrient cycling and provision, water regulation and purification, and habitat for functional and intrinsic biodiversity. Conservation agriculture (CA) is an alternative to enhance and optimize the provision of soil functions. Conservation Agriculture practice constitutes no-till combined with residue retention and crop rotation, CA is practiced to optimize available resources (soil, water and biological) whilst minimizing external inputs and soil degradation. Despite reported benefits, such as improved soil fertility, crop growth, better water infiltration, increased biological activity, decreased soil erosion and reduced labor, machinery use and fuel costs, CA is practiced only in less than 1% of cereal agricultural lands, well below the land areas of similar continental farming landscapes